2023
DOI: 10.1126/science.ade1662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hunger on neuronal histone modifications slow aging in Drosophila

Abstract: Hunger is an ancient drive, yet the molecular nature of pressures of this sort and how they modulate physiology are unknown. We find that hunger modulates aging in Drosophila . Limitation of branched-chain amino acids (BCAAs) or activation of hunger-promoting neurons induced a hunger state that extended life span despite increased feeding. Alteration of the neuronal histone acetylome was associated with BCAA limitation, and preventing these alterations abrogated the effect of BCAA limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…[ 71–74 ] To investigate the effects of alterations in BCAA metabolism on the aging process, we turned to Drosophila melanogaster , which has a shorter lifespan and shares conserved signaling pathways in cellular senescence and aging with mammals. [ 75–77 ] Furthermore, recent Drosophila studies demonstrated that BCAA‐restricted diet extends lifespan, [ 78,79 ] highlighting the role of BCAA metabolism during physiological aging in Drosophila .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 71–74 ] To investigate the effects of alterations in BCAA metabolism on the aging process, we turned to Drosophila melanogaster , which has a shorter lifespan and shares conserved signaling pathways in cellular senescence and aging with mammals. [ 75–77 ] Furthermore, recent Drosophila studies demonstrated that BCAA‐restricted diet extends lifespan, [ 78,79 ] highlighting the role of BCAA metabolism during physiological aging in Drosophila .…”
Section: Resultsmentioning
confidence: 99%
“…We used female fruit flies in these experiments, based on our preliminary findings that they were more responsive to the BCAA‐restricted diet and showed a greater lifespan extension compared to male flies, which is consistent with a previous study. [ 79 ] Strikingly, overexpression of either transporter significantly shortened fly lifespan (Figure 4c) and led to age‐related decline in climbing ability (Figure 4d). [ 83 ] Additionally, overexpression of dSlc6a15‐a or dSlc6a15‐b induced cellular senescent hallmarks, including upregulation of the cyclin‐dependent kinase inhibitor dacapo ( d p21) (Figure 4e), and increased expression of the inflammatory cytokine unpaired 2 ( Upd2 ) (Figure 4f) in elderly flies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in mouse and human studies, reducing dietary isoleucine or valine, but not leucine, enhances metabolic health in mice, while higher isoleucine intake in humans correlates with increased BMI 51 . In Drosophila , a decrease in isoleucine, but not valine, leucine, or their combinations, was found to be crucial for stimulating feeding behavior 52 . These suggest that individual BCAAs have specific influences on various phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Isoleucine restriction has recently garnered more attention than that of other amino acids, because of the generally protective effects that result from restricting its intake. When it is restricted in the diet, female flies live longer (Weaver et al 2023) and so do male and female heterogenous mice, who also have improved metabolic health (Green et al 2023). We also recently found that female flies subjected to two short bouts of isoleucine deprivation have extended lifespan (Fulton et al 2024).…”
Section: Discussionmentioning
confidence: 99%